A comprehensive assessment of single nucleotide polymorphisms associated with pancreatic cancer risk: A protocol for systematic review and network meta-analysis. Issue 24 (12th June 2020) - Ye, Zhuo-Miao; Li, Li-Juan; Zheng, Jing-Hui; Zhang, Chi; Lu, Yun-Xin; Tang, Youming
Abstract: Background: Single nucleotide polymorphisms (SNPs) have been inconsistently associated with pancreatic cancer (PC) risk. This meta-analysis aimed to synthesize relevant data on SNPs associated with PC. Methods: Databases were searched to identify association studies of SNPs and PC published through January 2020 from the databases of PubMed, Web of Science, Embase, Cochrane Library, China National Knowledge Infrastructure, the Chinese Science and Technology Periodical Database (VIP) and Wanfang databases. Network meta-analysis and Thakkinstian algorithm were used to select the most appropriate genetic model, along with false positive report probability (FPRP) for noteworthy associations. The methodological quality of data was assessed based on the STREGA statement Stata 14.0 will be used for systematic review and meta-analysis. Results: This study will provide a high-quality evidence to find the SNP most associated with pancreatic cancer susceptibility and the best genetic model. Conclusions: This study will explore which SNP is most associated with pancreatic cancer susceptibility. Registration: INPLASY202040023. Abstract : Supplemental Digital Content is available in the text